2018
DOI: 10.1080/10790268.2018.1543104
|View full text |Cite
|
Sign up to set email alerts
|

Community exercise programing and its potential influence on quality of life and functional reach for individuals with spinal cord injury

Abstract: Context/Objective: After an individual with a Spinal Cord Injury (SCI) participates in the initial rehabilitation process, they often experience limited access to physical therapy services and other fitness activities. The purpose of this study was to examine previously collected data for changes in quality of life (QoL) and functional reach in individuals with SCI following an 8-week community exercise program. Design: Secondary analysis of previously collected data. Setting: Community-based exercise program.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
4
9
0
1
Order By: Relevance
“…Of equal importance, these improved reaching abilities with ES were repeatable throughout the study. Our findings suggest that ES provides a therapeutic option for restoring functional trunk stability which is currently untreatable, or at best, marginally improved by long-term, strenuous exercise paradigms (Sliwinski et al, 2020). In addition to enabling supraspinal control over motor functions, ES-enabled motor functions are thought to facilitate a more physiological pattern of motor unit recruitment when compared to currently-available NMES systems (Henneman, 1957;Henneman et al, 1965;Maffiuletti, 2010;Bickel et al, 2011).…”
Section: Therapeutic Potential Of Esmentioning
confidence: 88%
“…Of equal importance, these improved reaching abilities with ES were repeatable throughout the study. Our findings suggest that ES provides a therapeutic option for restoring functional trunk stability which is currently untreatable, or at best, marginally improved by long-term, strenuous exercise paradigms (Sliwinski et al, 2020). In addition to enabling supraspinal control over motor functions, ES-enabled motor functions are thought to facilitate a more physiological pattern of motor unit recruitment when compared to currently-available NMES systems (Henneman, 1957;Henneman et al, 1965;Maffiuletti, 2010;Bickel et al, 2011).…”
Section: Therapeutic Potential Of Esmentioning
confidence: 88%
“…Given the greater impact on trunk stability of those with higher-level injuries, 44,49 improvements were the greatest in the two individuals with cervical injuries. Sliwinski et al, 19 found a positive change in functional reach improves postural control and seated balance, skills that are vital for individuals with SCI. 19 With the exception of subject 8, all subjects improved beyond the MDC values for mFR used for comparison in this study.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous retrospective study of a communitybased exercise program, specifically the Spinal Mobility X class (SMX), has shown a positive effect on function and quality of life for people with SCI. 19 In addition to regular exercise, IMT can provide additional benefit for individuals with SCI. 8,9,15 To decrease risk for respiratory complications, resistive respiratory training (RRT) can be included in an exercise program to potentially decrease secondary health complications.…”
Section: Introductionmentioning
confidence: 99%
“…Em pessoas acometidas com LM, a incapacidade funcional pode provocar graus variados de dependência no que se refere às atividades de vida diária (AVDs), principalmente em relação ao autocuidado, controle de esfíncteres, mobilidade, entre outras (TULSKY et al, 2015). A independência funcional influencia o desempenho nas atividades cotidianas, no potencial desempenho ocupacional e na participação social (SLIWINSKI et al, 2020).…”
Section: Introductionunclassified